Thermal Performance and Pressure drop of the Corrugated tubes: Thermal Performance and Pressure drop of the Corrugated tubes - อรุณรัตน์ คณิต; ด้วงทองสุข วีระพันธ์ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2019)
The corrugated tube enhances the heat transfer by generating secondary flow, promoting fluid turbulence, and increasing the heat transfer area. The corrugated tube can be used instead of smooth tube in all types of heat exchanger. As a result, the thermal performance of heat exchanger can be improved. The geometric factors affecting on the heat transfer and pressure drop of this tube are the corrugation pitch, helix angle, corrugation depth, and number of start. For the single-phase flow, the experiments were conducted at the Reynolds number between 100 and 100,000. The test fluids were water, air, oil, and ethylene glycol. The values of Nusselt number ratio were between 1 and 4.7 and the friction factor ratio were between 1.05 and 15. In case of two-phase flow, the test fluids were R-22, R407C, R-134a and R-404a. The results showed that the corrugated tube increases the heat transfer coefficient and the frictional pressure drop in the range of 5-100 and 10-300% compared to that of smooth tube, respectively.